Arab Family Studies : Critical Reviews - Joseph, Suad (Book collections on Project MUSE., 2018)
This review of the literature on Arab families captures the major theories, methods, and case studies carried out on Arab families over the past half to one century. The book offers a country by country critical assessment of the scholarship on Arab families.